IMPACTOS AMBIENTALES Y SUS EFECTOS EN EL DESARROLLO Y TURISTICO EN EL SECTOR EL PALMAR-LA MANA 2022 - Quintana Herrera, Tahis Oderey (2022)
The environmental impacts directly influence the Tourism Development of the areas where it is carried out, which is why studies must be carried out to analyze the environmental impacts generated by both Tourism and the inhabitants of the area. The objective of this research is to carry out a study of the environmental impacts and their effects on the tourist development of the El Palmar Sector. La Mana, year 2022, which presents, for various reasons, either due to the lack of budgetary support, management and maintenance of its tourism sector, as well as the mismanagement of waste, a risk of environmental impact in the area, which enjoys a wealth of natural resources, therefore, the tourism sector has not found its maximum potential. For the development of this study, qualitative, inductive-deductive methods, and bibliographic-documentary research were applied, which describe and explain how it will contribute to its tourism development.